A review of the value of quadrivalent influenza vaccines and their potential contribution to influenza control. Issue 7 (3rd July 2017) - Ray, Riju; Dos Santos, Gaël; Buck, Philip O.; Claeys, Carine; Matias, Gonçalo; Innis, Bruce L.; Bekkat-Berkani, Rafik
ABSTRACT: The contribution of influenza B to the seasonal influenza burden varies from year-to-year. Although 2 antigenically distinct influenza B virus lineages have co-circulated since 2001, trivalent influenza vaccines (TIVs) contain antigens from only one influenza B virus. B-mismatch or co-circulation of both B lineages results in increased morbidity and mortality attributable to the B lineage absent from the vaccine. Quadrivalent vaccines (QIVs) contain both influenza B lineages. We reviewed currently licensed QIVs and their value by focusing on the preventable disease burden. Modeling studies support that QIVs are expected to prevent more influenza cases, hospitalisations and deaths than TIVs, although estimates of the case numbers prevented vary according to local specificities. The value of QIVs is demonstrated by their capacity to broaden the immune response and reduce the likelihood of a B-mismatched season. Some health authorities have preferentially recommended QIVs over TIVs in their influenza prevention programmes.